Jakub z Szadka – ksiądz, dyplomata i prawnik (ur. około 1412 r. w Szadku – zm. 28 października 1487 r. w Krakowie) - Marszał, Tadeusz (Biuletyn Szadkowski, 2008)
Jakub of Szadek is one of the many people from this small town (now in Central Poland), who in XV century came to Cracow to study, and played a significant role in the life of both the Jagiellonian University and the country. He is chiefly known for his diplomatic activity – being an eminent lawyer, he took part in many diplomatic missions during the 13-year war with the Teutonic Knights. He had a major part in the preparation of foundations for the signing of the peace treaty in Toru in 1466. In the years 1474–1476 he performed the function of Rector of Cracow Academy, contributing greatly to the extension of Collegium Minor. In 1476 he was appointed to the high position of vicar general in Cracow diocese. Jakub of Szadek is the co-author of a new approach to the theory of the rights of nations, and human rights, with reference to natural rights, the Gospel and the teachings of Popes and oecumenical councils. He is also one of Polish creators of international law, whose intensive development falls in Poland on XV century. In addition, he deserves the credit for invoking the nationality principle in international negotiations (the principle acknowledging the fact that particular regions are inhabited by people of Polish origin and speaking Polish language, who gave Polish names to cities, mountains, rivers and settlements). At least two texts of his speeches has been preserved until today thanks to J. Długosz, who was his friend. Jakub of Szadek died in 1487.